Literasi Digital dan Pemanfaatan Media Sosial dalam Pembelajaran: Program Pendampingan Guru di SMK Permas Jaya 2 dan Sekolah Indonesia Johor Bahru, Malaysia - Dek Ngurah Laba Laksana; Sally Cahyati; Rosalind Ahju (Universitas Negeri Gorontalo, 2025)
Improving the level of training and ability of educators to create technology-integrated instruction has become important in the current digital age, especially at Sekolah Indonesia Johor Bahru (SIJB) and Sekolah Menengah Kebangsaan Permas Jaya 2 (SMK Permas Jaya 2) in Malaysia. Making the best use of social media and digital apps in their teaching and learning processes presents difficulties for both institutions. Thirteen teachers from SMK Permas Jaya 2 and ten from SIJB participated in this community service program, which aimed to enhance their knowledge and practical abilities in using digital and artificial intelligence (AI) programs such Canva, ChatGPT, Perplexity, Grammarly, and Book Creator. Pretest and post test assessments were used in conjunction with lessons, discussions, demonstrations, and practical exercises. According to pretest results, the majority of teachers understood digital literacy at a moderate level, but they still lacked the practical abilities to use digital apps. The majority of teachers advanced to the